microRNAs in Cardiovascular Disease: Small Molecules but Big Roles - Yan, Bingqian; Wang, Huijing; Tan, Yao; Fu, Wei (Current Topics in Medicinal Chemistry, 2019)
microRNAs (miRNAs) are an evolutionarily conserved class of small single-stranded noncoding RNAs. The aberrant expression of specific miRNAs has been implicated in the development and progression of diverse cardiovascular diseases. For many decades, miRNA therapeutics has flourished, taking advantage of the fact that miRNAs can modulate gene expression and control cellular phenotypes at the posttranscriptional level. Genetic replacement or knockdown of target miRNAs by chemical molecules, referred to as miRNA mimics or inhibitors, has been used to reverse their abnormal expression as well as their adverse biological effects in vitro and in vivo in an effort to fully implement the therapeutic potential of miRNA-targeting treatment. However, the limitations of the chemical structure and delivery systems are hindering progress towards clinical translation. Here, we focus on the regulatory mechanisms and therapeutic trials of several representative miRNAs in the context of specific cardiovascular diseases; from this basic perspective, we evaluate chemical modifications and delivery vectors of miRNA-based chemical molecules and consider the underlying challenges of miRNA therapeutics as well as the clinical perspectives on their applications.
Keywords: Cardiovascular disease